PROGRAM PENGENALAN ALAT KUMBUNG JAMUR CERDAS BERBASIS INTERNET OF THINGS - Elsa Elvira Awal; Anis Fitri Nur Masruriyah (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
The environment that affects the growth and yield of mushrooms is one of them is the thickness of planting media. Different thicknesses of planting media will produce different temperature conditions. Mushrooms grow in locations that have enough oxygen and grow optimally at 32°-35°C and 80-90% humidity for the vegetative/mycelium phase, while in the generative/body formation phase the fruit is optimal at 30°-32°C and humidity is 85-95%. Based on this explanation, it is necessary to introduce intelligent mushroom kumbuh tool with internet of things to help the cultivation of mushrooms using fuzzy logic methods. The tool can control ioT-based temperature and humidity so that mushroom farmers can monitor mushrooms through the web, so that mushroom farmers can understand that smart mushrooms are able to provide information about temperature and humidity conditions in real time.